PENGEMBANGAN MODUL EDUKASI UNTUK MENINGKATKAN NILAI KARAKTER TANGGUNG JAWAB PADA SISWA SMP N 32 PEKANBARU - Adellia Adellia; Elni Yakub; Triumari Triumari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to develop an educational module to increase the value of the character of responsibility for students of SMP N 32 Pekanbaru. This material is prepared using R&D research and development methods. The assessment module is reviewed from the physical / appearance aspects, preliminary aspects, service aspects, content aspects, task aspects, and summary aspects. The educational module material was validated by 2 lecturers of the UR FKIP BK, and 2 Guidance and Counseling Teachers. The educational material consists of 4 modules, namely, module 1: Responsibilities, module 2: Benefits of responsibility, module 3: Shaping responsibility, module 4: Inspirational stories about responsibilities. From the value given by the validator, the calculation results for the physical / display aspects obtained a score of 87.5 very good categories, the preliminary aspects obtained a score of 81.25 in the very good category, the service aspect obtained a score of 87.5 for the very good category, the content aspect obtained a score 82.5 very good category, the task aspect got a score of 87.5 very good category, and the summary aspect got a very good score of 85 categories, so that for the total aspects of the material assessment it shows that the material developed has met the expected criteria by obtaining a score of 85, 25 which belongs to the very good category.Key words: Education Module,R&D, Responsibilities